Estudio de la inimputabilidad por trastornos mentales en la legislación penal ecuatoriana - Hidalgo Navarrete, Samira Yolanda (2024)
This thesis explores the complex relationship between mental health and the penal legal system in Ecuador, concerning the accountability and criminal responsibility of individuals with mental disorders. The central problem and objective of this research is to establish whether the absence of a clear enumeration of mental disorders that can be considered as a cause of non-imputability in the Ecuadorian legal system has a significant impact on the administration of justice. The methodology used in this work was based on a mixed approach through a documentary review of legal regulations, analysis of judicial cases, interviews, and surveys with legal and mental health professionals. An exploratory descriptive depth level was used to obtain initial knowledge and a general understanding of the problem, identifying relevant aspects and different factors involved. Additionally, the principal scientific method, the socio-legal method, which focuses on the interpretation of texts and sentences, was applied. The inductive method was also used to collect empirical data on specific cases of people with mental disorders and analyze them to identify broader trends regarding accountability in the Ecuadorian legal system. The most relevant results of the research revealed two illustrative cases that highlight the importance of considering the mental health of the accused in the judicial process and the need for greater awareness within the judicial system. Likewise, difficulties in identifying mental disorders were recognized, emphasizing the need to address deficiencies in legislation and professional training to ensure a more equitable and effective legal system for people with mental disorders.